A polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system loaded with mesoporous silica bai1, preparation method and application

CN122894306APending Publication Date: 2026-10-13FOURTH MILITARY MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611128105.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

BAI1(一种选择性BAX寡聚化抑制剂)具有抑制mtDNA泄漏、缓解细胞衰老的潜力,但其疏水性强、局部透皮吸收差,难以在伤口部位实现长效、可控的递送

Benefits of technology

[0022]本发明首次将BAX别构抑制剂BAI1负载于介孔二氧化硅纳米粒中,提高了药物稳定性和分散性;并进一步包封于聚乙烯醇-海藻酸钠-单宁酸-硼砂复合水凝胶中,形成了介孔二氧化硅纳米颗粒内载疏水药物并均匀分散于水凝胶三维网络中的多级结构,水凝胶网络通过硼砂与PVA的硼酸酯键、TA的酚羟基、PVA/SA的氢键及疏水作用形成动态交联,不仅能够避免药物在交联过程中失活或泄漏;而且能够赋予材料自愈合性和剪切变稀的可注射性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894306A_ABST
    Figure CN122894306A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of biomedical materials, and aims at the problem that the existing dressing does not have the ability to actively regulate the wound microenvironment, only provides physical barrier or moisturizing effect, and cannot reverse VEC aging and dysfunction. The present application discloses a polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system loaded with BAI1 mesoporous silica, a preparation method and application. The composite delivery system comprises a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel and BAI1-mesoporous silica freeze-dried powder encapsulated in the composite hydrogel. The polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel is formed by cross-linking polyvinyl alcohol, sodium alginate, tannic acid and borax. The BAI1-mesoporous silica freeze-dried powder comprises mesoporous silica nanoparticles and BAI1 loaded in the mesopores thereof. The present application can alleviate cell aging, restore vascular generation function, inhibit inflammatory response, and accelerate the healing of diabetic and infected wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel loaded with BAI1 mesoporous silica, its preparation method, and its application. Background Technology

[0002] Diabetic foot ulcer (DFU) is one of the most common and serious complications of diabetes, affecting approximately 15-25% of diabetic patients. More than 85% of non-traumatic lower limb amputations are associated with DFU.

[0003] Currently, commonly used wound dressings in clinical practice include traditional gauze, foam dressings, hydrocolloids, silver ion-containing dressings, and advanced dressings containing growth factors (such as recombinant epidermal growth factor gel). However, most existing dressings lack the ability to actively regulate the wound microenvironment, providing only a physical barrier or moisturizing effect, and cannot reverse vascular endothelial cell (VEC) aging and dysfunction. Growth factor dressings hinder wound drainage, affect the wound microenvironment, cause abnormal tissue proliferation, increase the risk of infection, are expensive, and have poor stability. In chronic wounds, they are easily degraded due to excessive protease activity, resulting in limited clinical efficacy. Although some studies have attempted to load anti-inflammatory or pro-angiogenic drugs into hydrogels, there is a lack of targeted intervention for the core pathological link of VEC aging, especially a lack of effective delivery systems that can inhibit mitochondrial DNA (mtDNA) leakage and excessive activation of the cGAS-STING pathway. BAI1 (a selective BAX oligomerization inhibitor) has the potential to inhibit mtDNA leakage and alleviate cell aging, but its strong hydrophobicity and poor local transdermal absorption make it difficult to achieve long-term, controllable delivery at the wound site.

[0004] Therefore, it is necessary to provide a novel composite hydrogel dressing, its preparation method, and its application that can safely and efficiently carry and continuously release the hydrophobic anti-aging drug BAI1, possess good tissue adhesion, self-healing, and anti-infection capabilities, and can reduce cell aging and promote the healing of diabetic wounds by inhibiting the mtDNA / cGAS-STING pathway in skin wound tissue cells. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system, preparation method and application of BAI1-loaded mesoporous silica.

[0006] The first aspect of the present invention provides a polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system loaded with BAI1 mesoporous silica, the composite delivery system comprising a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel and BAI1-mesoporous silica lyophilized powder encapsulated therein.

[0007] The polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel is formed by cross-linking polyvinyl alcohol (PVA), sodium alginate (SA), tannic acid (TA) and borax.

[0008] The BAI1-mesoporous silica freeze-dried powder includes mesoporous silica nanoparticles and BAI1 loaded in its mesopores.

[0009] Furthermore, the mass ratio of polyvinyl alcohol, sodium alginate, tannic acid and borax is 5-15 : 1-5 : 0.5-3 : 0.5-2.

[0010] Furthermore, the mass ratio of BAI1 to mesoporous silica nanoparticles is 0.5-2:1.

[0011] A second aspect of the present invention provides a method for preparing the composite delivery system according to any one of the above claims, comprising:

[0012] Weigh BAI1 and mesoporous silica nanoparticles according to the mass ratio, and prepare BAI1 solution and mesoporous silica dispersion respectively;

[0013] BAI1 solution was added to mesoporous silica dispersion and stirred at room temperature for 24 hours. After centrifugation and washing multiple times, cryoprotectant and deionized water were added to the precipitate, mixed well, and pre-frozen at -80℃ for 4 hours. Then, it was freeze-dried to obtain BAI1-mesoporous silica freeze-dried powder.

[0014] Weigh out polyvinyl alcohol, sodium alginate, tannic acid and borax according to the mass ratio. Prepare polyvinyl alcohol solution and borax solution respectively. Add sodium alginate to polyvinyl alcohol solution and stir for 1 hour. Then add tannic acid and continue stirring for 30 minutes. Adjust the pH to 8.0 to obtain a mixed solution.

[0015] BAI1-mesoporous silica lyophilized powder was added to the mixed solution and stirred for 30 minutes. Then, borax solution was added while stirring. After the addition was completed, stirring was continued for 1 minute and the mixture was allowed to stand for 30 seconds to obtain a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel with BAI1-mesoporous silica lyophilized powder inside, which is the composite delivery system.

[0016] Furthermore, the mass ratio of the cryoprotectant to the mesoporous silica nanoparticles is 0.2:1.

[0017] Furthermore, the freeze-drying pressure is <10 Pa, and the freeze-drying temperature and time are -50°C and 48 hours, respectively.

[0018] Furthermore, the mass ratio of the BAI1-mesoporous silica lyophilized powder to polyvinyl alcohol is 1-6 : 5-15.

[0019] A second aspect of the present invention provides the use of the composite delivery system described in any of the above claims in the preparation of dressings for the repair of diabetic wounds.

[0020] A third aspect of the present invention provides a dressing for the repair of diabetic wounds, comprising the composite delivery system described in any of the preceding claims.

[0021] Compared with the prior art, the advantages of this invention are as follows:

[0022] This invention is the first to load the BAX allosteric inhibitor BAI1 into mesoporous silica nanoparticles, improving drug stability and dispersibility. Furthermore, it encapsulates the drug within a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel, forming a multi-level structure where the hydrophobic drug is uniformly dispersed within the mesoporous silica nanoparticles in a three-dimensional hydrogel network. This hydrogel network dynamically crosslinks through borax-PVA ester bonds, phenolic hydroxyl groups of TA, hydrogen bonds between PVA and SA, and hydrophobic interactions. This not only prevents drug inactivation or leakage during crosslinking but also endows the material with self-healing properties and shear-thinning injectability.

[0023] This invention utilizes topical application. After BAI1-mesoporous silica is released from the composite hydrogel, it is taken up by cells in wound tissue, thereby inhibiting BAX-mediated mtDNA leakage, blocking cGAS-STING pathway activation, reducing cellular senescence, restoring angiogenesis, and suppressing inflammatory responses, thus accelerating the healing of diabetic and infected wounds. Furthermore, animal experiments have demonstrated its superior efficacy compared to commercially available growth factor gels, indicating clear clinical application potential. Attached Figure Description

[0024] Figure 1 A schematic diagram of the composite delivery system BAI1-PSTB;

[0025] Figure 2 Transmission electron microscopy images of BAI1@MSNs;

[0026] Figure 3 The ultraviolet spectrum of BAI1@MSNs;

[0027] Figure 4 Scanning electron microscope image of the BAI1-PSTB composite delivery system;

[0028] Figure 5 Rheological diagram of the composite delivery system BAI1-PSTB;

[0029] Figure 6 The image shows the adhesion test results of the BAI1-PSTB composite delivery system.

[0030] Figure 7 Figure showing the injectability and adhesion test results of the BAI1-PSTB composite delivery system;

[0031] Figure 8 Release curves of the combined delivery system BAI1-PSTB in PBS, 50 mM glucose, and SWE;

[0032] Figure 9 Degradation curves of the composite delivery system BAI1-PSTB;

[0033] Figure 10 The results show a comparison between the BAI1-PSTB composite delivery system and blank PSTB hydrogel in the application of skin wounds in diabetic mice; among them, Figure 10 In the figure, A represents a representative wound photograph of each group of mice at different time points; Figure 10 B in the figure represents the statistical results of the wound size of each group; Figure 10 C in the figure represents the statistical result of the percentage of remaining wound area in each group; Figure 10 D in the figure represents the HE staining results of the wound tissue on the 14th day after surgery in each group; Figure 10 E represents the Masson trichrome staining results of wound tissue on postoperative day 14 in each group; Figure 10 F in the figure represents the CD31 immunohistochemical staining results of the wound tissue on postoperative day 14 in each group; Figure 10 The GI values ​​represent the immunohistochemical staining results of BAX, STING, and p16 in the wound tissue on postoperative day 14.

[0034] Figure 11 The results show a comparison between the BAI1-PSTB composite delivery system and growth factor gel in the application of infected wounds; among them, Figure 11 In the figure, A represents a representative wound photograph of each group of mice at different time points; Figure 11 In the figure, B represents the statistical results of the wound size for each group; Figure 11 C in the figure represents the statistical result of the percentage of remaining wound area in each group; Figure 11 The DF values ​​represent the HE, Masson, and CD31 immunohistochemical staining results of the wound tissue on postoperative day 14 in each group. Detailed Implementation

[0035] The technical solutions of the embodiments of this application are described below with reference to the accompanying drawings. It should be understood that the described embodiments are only some embodiments of this application, and not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are all within the protection scope of this application.

[0036] In the following examples, mesoporous silica nanoparticles (MSNs) were purchased from Ruixi (Xi'an); BAI1 was purchased from MedChemExpress; polyvinyl alcohol (PVA) was purchased from Aladdin; sodium alginate (SA) was purchased from Aladdin; tannic acid (TA) was purchased from Aladdin; borax ( Purchased from Aladdin.

[0037] Example 1

[0038] This invention provides a polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system loaded with BAI1 mesoporous silica. The composite delivery system includes a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel and BAI1-mesoporous silica lyophilized powder encapsulated therein.

[0039] The polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel is formed by cross-linking polyvinyl alcohol, sodium alginate, tannic acid and borax;

[0040] The BAI1-mesoporous silica freeze-dried powder includes mesoporous silica nanoparticles and BAI1 loaded in its mesopores.

[0041] Specifically, the mass ratio of polyvinyl alcohol, sodium alginate, tannic acid and borax is 8:2:1:1.

[0042] Specifically, the mass ratio of BAI1 to mesoporous silica nanoparticles is 0.5:1.

[0043] like Figure 1 As shown, this embodiment of the invention also provides a method for preparing the above-mentioned composite delivery system, specifically including:

[0044] BAI1 and mesoporous silica nanoparticles were weighed according to the mass ratio and prepared into BAI1 solution and mesoporous silica dispersion, respectively. Specifically, 2 parts by weight of MSNs were dispersed in 100 parts by weight of deionized water and ultrasonically dispersed for 30 min (power 200 W, frequency 40 kHz) to obtain MSN dispersion. 1 part by weight of BAI1 was dissolved in 100 parts by weight of ethanol-methanol mixed solvent (v / v=1:1) and stirred until completely dissolved (room temperature, 500 rpm, 10 min) to obtain BAI1 solution.

[0045] BAI1 solution was slowly added dropwise to MSN dispersion (dropping rate 1 mL / min), and stirred vigorously at room temperature (20-25℃) (1000 rpm) for 24 h. After the reaction was completed, the precipitate was collected by centrifugation at 10,000 rpm for 10 min. The precipitate was washed three times with deionized water, and centrifuged again each time (10,000 rpm, 10 min) to remove unloaded free BAI1. 0.2 parts by weight of cryoprotectant and a small amount of deionized water were added to the washed precipitate, mixed well, and pre-frozen at -80℃ for 4 hours. Then, it was freeze-dried to obtain BAI1-mesoporous silica lyophilized powder (BAI1@MSN lyophilized powder).

[0046] Specifically, the cryoprotectant is trehalose; the freeze-drying pressure is <10 Pa, and the freeze-drying temperature and time are -50℃ and 48 hours, respectively.

[0047] Weigh out polyvinyl alcohol (PVA), sodium alginate, tannic acid, and borax according to the specified mass ratio. Prepare PVA and borax solutions separately. Add sodium alginate to the PVA solution and stir for 1 hour. Then add tannic acid and continue stirring for 30 minutes. Adjust the pH to 8.0 to obtain a mixed solution. Specifically, add 8 parts by weight of PVA to 100 parts by weight of deionized water and heat in a 90°C water bath with mechanical stirring (500 rpm) for 2 hours to obtain a homogeneous PVA solution. Dissolve 1 part by weight of borax in 5 parts by weight of deionized water to obtain a borax solution. After the PVA solution cools to room temperature (25°C), add 2 parts by weight of SA and continue stirring (500 rpm) for 1 hour until completely dissolved. Then add 1 part by weight of TA and continue stirring (500 rpm) for 30 minutes until dissolved. Adjust the pH of the solution dropwise with 1 M NaOH solution to 8.0 (using a pH meter) to obtain a mixed solution.

[0048] Three parts by weight of BAI1@MSN lyophilized powder were added to the mixed solution and magnetically stirred (500 rpm) for 30 min to uniformly disperse the nanoparticles. Then, borax solution was added dropwise (0.5 mL / min) while stirring rapidly (800 rpm). After the addition was completed, stirring was continued for 1 min, and the mixture was allowed to stand for 30 seconds to obtain a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel delivery system (BAI1-PSTB) with BAI1-mesoporous silica lyophilized powder encapsulated inside.

[0049] Example 2

[0050] This embodiment provides a polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system and its preparation method for BAI1-loaded mesoporous silica. The structure and preparation method of the composite delivery system in this embodiment are basically the same as those in Example 1, except that the mass ratio of polyvinyl alcohol, sodium alginate, tannic acid, and borax is 5:1:0.5:0.5; the mass ratio of BAI1 to mesoporous silica nanoparticles is 1:1; and the mass ratio of BAI1-mesoporous silica lyophilized powder to polyvinyl alcohol is 1:5.

[0051] Specifically, the mass ratio of polyvinyl alcohol, sodium alginate, tannic acid and borax is 8:2:1:1.

[0052] Specifically, the mass ratio of BAI1 to mesoporous silica nanoparticles is 0.5:1.

[0053] The mass ratio of BAI1-mesoporous silica lyophilized powder to polyvinyl alcohol is 3:8.

[0054] Example 3

[0055] This embodiment provides a polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system and its preparation method for BAI1-loaded mesoporous silica. The structure and preparation method of the composite delivery system in this embodiment are basically the same as those in Example 1, except that the mass ratio of polyvinyl alcohol, sodium alginate, tannic acid, and borax is 15:5:3:2; the mass ratio of BAI1 to mesoporous silica nanoparticles is 2:1; and the mass ratio of BAI1-mesoporous silica lyophilized powder to polyvinyl alcohol is 6:15.

[0056] The key performance characteristics and tests of the polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system loaded with BAI1 prepared in Example 1 of this invention are as follows.

[0057] 1. Physical and chemical properties

[0058] 1.1 Characterization of BAI1@MSN lyophilized powder

[0059] 1.1.1 Hydrodynamic size and zeta potential

[0060] The BAI1@MSN lyophilized powder prepared in Example 1 of this invention was diluted with deionized water to 0.1 mg / mL. The particle size and zeta potential were measured using a dynamic light scattering instrument (NanoBrook 90Plus PALS). Each sample was measured three times, and the average value of the measurement results was taken. The results are shown in Table 1 below.

[0061] Table 1 Particle size and Zeta potential of BAI1@MSN lyophilized powder

[0062]

[0063] As shown in Table 1, the average particle size of the BAI1@MSN lyophilized powder prepared in Example 1 of this invention is 89.20±2.32nm; the average value of the Zeta potential is -6.39±0.78mV, and the PDI = 0.16, indicating that the BAI1@MSN lyophilized powder prepared in Example 1 of this invention has good dispersibility.

[0064] 1.1.2 Microstructure

[0065] The microstructure of the BAI1@MSN lyophilized powder prepared in Example 1 of this invention was characterized by transmission electron microscopy (TF20, FEI, USA), and the results are as follows: Figure 2 As shown, through Figure 2 As can be seen, the BAI1@MSN lyophilized powder prepared in Example 1 of this invention exhibits a uniform spherical or near-spherical morphology with a relatively concentrated particle size distribution, consistent with the average particle size of approximately 89 nm measured by dynamic light scattering. Obvious mesoporous channels are observed on the particle surface (light-colored striped areas in the figure), indicating that the MSN carrier has an ordered mesoporous structure, providing ample space for the physical adsorption loading of BAI1 drug. Furthermore, the particles show good dispersion, with no obvious aggregation observed, demonstrating that the loading process of this invention can maintain the monodisperse state of the nanoparticles, which is beneficial for subsequent uniform dispersion in the hydrogel system and stable drug release.

[0066] 1.1.3 Drug Load Validation

[0067] The absorbance of BAI1@MSN lyophilized powder was measured using a UV-Vis spectrophotometer (TU-1810), and the results are as follows: Figure 3 As shown. (Through) Figure 3 The pure MSN carrier showed no obvious characteristic absorption peak in the 200-400 nm wavelength range, while the free BAI1 drug showed a significant characteristic absorption peak at approximately 254 nm. When BAI1 was loaded into the mesopores of MSN and then freeze-dried, the BAI1@MSN complex still retained a significant absorption peak at the same wavelength, and the absorption intensity was positively correlated with the BAI1 loading amount. This result confirms that BAI1 was successfully loaded into the pores of mesoporous silica nanoparticles, rather than through simple physical mixing, and also verifies the effectiveness of the loading method of this invention.

[0068] 1.2 Characterization of the BAI1-PSTB composite delivery system

[0069] 1.2.1 The microstructure of the BAI1-PSTB composite delivery system prepared in Example 1 of this invention was characterized by scanning electron microscopy (Sigma 300, ZEISS, Germany, accelerating voltage 5 kV). The results are as follows: Figure 4 As shown, through Figure 4 The BAI1-PSTB composite delivery system exhibits a typical three-dimensional porous network structure with a relatively uniform pore size distribution and continuous, intact pore walls. BAI1@MSN nanoparticles (white bright spots in the image) are uniformly dispersed and anchored on the pore surface and within the pores of the hydrogel network, with no obvious nanoparticle aggregation observed. This microstructure indicates that the introduction of MSN nanoparticles did not disrupt the integrity of the hydrogel's framework, and that the three-dimensional network of the hydrogel effectively restricts nanoparticle migration, which is beneficial for achieving localized sustained drug release.

[0070] 1.2.2 Calculation of swelling ratio

[0071] The BAI1-PSTB composite delivery system, weighed (W0), was immersed in PBS (pH 7.4, 37℃) for 24 h. After removal, the surface moisture was absorbed with filter paper, and the system was weighed (W1). The swelling rate was then calculated using the formula: Swelling rate = (W1 - W0) / W0 × 100%. Based on the actual weighing results, W0 = 0.2926 and W1 = 0.5971, the swelling rate = (0.5971 - 0.2926) / 0.2926 × 100% = 104%.

[0072] 1.2.3 Rheological Measurement

[0073] The rheological properties of the BAI1-PSTB composite delivery system prepared in Example 1 of this invention were measured using an Anton Paar MCR302 rheometer. The parameters were set as follows: parallel plate rotor (8 mm diameter), gap 1 mm, strain 0.5%, frequency sweep 0.1-10 rad / s. The storage modulus G' and loss modulus G'' were recorded. The results are as follows: Figure 5 As shown. (Through) Figure 5 The results showed that the G' value was consistently significantly higher than the G'' value across the entire scanning frequency range, and both G' and G'' exhibited weak frequency dependence. This indicates that the BAI1-PSTB composite hydrogel possesses typical elastic solid behavior, meaning it forms a stable cross-linked network structure. This rheological property endows the hydrogel with good mechanical strength, enabling it to resist external deformation when covering wounds, maintaining an intact covering layer and providing a stable physical microenvironment conducive to wound healing.

[0074] 1.2.4 Adhesion Test

[0075] like Figure 6As shown, the BAI1-PSTB composite delivery system prepared in Example 1 of this invention was coated into an EP tube. The EP tube was inverted, and the adhesion between the BAI1-PSTB composite delivery system and the EP tube was observed. The BAI1-PSTB composite delivery system was coated onto the surface of a glove, and the adhesion of the BAI1-PSTB composite delivery system to a moving joint was observed by bending the finger. Figure 6 The results showed that after coating the inner wall of an EP tube with the BAI1-PSTB composite delivery system and then inverting the tube, the hydrogel adhered firmly to the tube wall without slipping. Furthermore, when the hydrogel was coated onto the surface of a glove's knuckles and subjected to bending movements, the hydrogel remained tightly adhered at the joint movement area without cracking or detachment. These results clearly demonstrate that the BAI1-PSTB composite delivery system possesses excellent tissue adhesion and flexibility, adapting to the minute deformations of skin wounds, especially in moving areas such as joints, ensuring long-term stable adhesion of the dressing to the wound surface. This is crucial for sustained drug release during wound healing.

[0076] 1.2.5 Injectability and self-healing properties test

[0077] like Figure 7 As shown, the BAI1-PSTB composite delivery system prepared in Example 1 of this invention was injected into the bottom of a culture dish using a syringe, and the injectability of the BAI1-PSTB composite delivery system was observed; after the two segments of the BAI1-PSTB composite delivery system were brought into contact, they were left to stand for 5 minutes to observe the fusion. Figure 7 The results show that the BAI1-PSTB composite delivery system can be smoothly extruded using a conventional syringe. After injection, it quickly forms and maintains its shape on the receiving surface, indicating its shear-thinning injectable properties, making it suitable for filling irregularly shaped deep or sinus tract wounds. Furthermore, when two independent segments of the BAI1-PSTB composite delivery system are cut into pieces and left to stand for 5 minutes, the interface gradually blurs and fuses into a single unit, demonstrating the system's excellent self-healing ability. This self-healing property stems from the dynamic reversible cross-linking properties of the borate ester bonds. When the hydrogel is cut or locally damaged, new cross-links can reform at the contact surface, restoring the material's integrity and function. This is crucial for the long-term stability of the dressing on dynamic wound surfaces.

[0078] 1.2.6 Drug Release Test

[0079] One mL of the BAI1-PSTB composite delivery system prepared in Example 1 of this invention was immersed in 10 mL of release medium (PBS, enzyme-containing simulated wound fluid SWE, or high-glucose medium) and shaken at 37°C (100 rpm). 200 μL samples were taken at predetermined time points, and the BAI1 concentration was determined by HPLC. HPLC conditions: C18 column (4.6 × 250 mm, 5 μm), mobile phase acetonitrile:water (60:40, v / v), flow rate 1 mL / min, detection wavelength 254 nm, column temperature 30°C.

[0080] pass Figure 8 The results show that the BAI1-PSTB composite delivery system prepared in Example 1 of this invention exhibits significant differences in BAI1 release behavior in different media. Specifically, BAI1 release is faster in a high-glucose environment, followed by enzyme-mimicking wound fluid (SWE), and relatively slower in PBS. This release characteristic is highly compatible with the application scenario of this invention for diabetic wounds. The microenvironment of diabetic wounds is typically characterized by high glucose and high protease activity. This BAI1-PSTB composite delivery system can responsively accelerate the release of BAI1, achieving an intelligent drug delivery mode of on-demand release, which is beneficial for precisely exerting therapeutic effects in the pathological microenvironment.

[0081] 1.2.7 Drug Degradation Test

[0082] The BAI1-PSTB composite delivery system prepared in Example 1 of this invention was fabricated into a uniform shape, such as a disc or cylinder, with dimensions of 8-10 mm in diameter and 2-3 mm in thickness, to obtain a hydrogel. The initial mass (W0) of the hydrogel was then recorded, and the initial dimensions could be measured simultaneously. The hydrogel was then immersed in 10 mL of a common buffer solution (PBS, pH 7.4) to simulate physiological conditions. The hydrogel was then removed at different time points (0, 1, 3, 6, 12, 24 h, and 2, 3, 5, 7, 14, 21, 28 d), the surface moisture was blotted dry with filter paper, and the weight (W0) was measured. t At least three groups should be tested each time. Then calculate the degradation rate using the formula: Degradation rate (%) = (W0 - W) t ) / W0×100%. The result is as follows Figure 9 As shown.

[0083] pass Figure 9This indicates that the BAI1-PSTB composite delivery system prepared in Example 1 of this invention degrades relatively slowly in the early stages (0-7 days), maintaining a high level of mass retention, which is beneficial for providing continuous drug protection during the early inflammatory and proliferative phases of wound healing. After day 7, the degradation rate accelerates, and by day 28, most of the hydrogel has degraded. This slow-then-fast degradation pattern matches the phased needs of wound healing. In the early stages, a stable drug release barrier is required, while in the later stages, as new tissue grows in, the hydrogel gradually degrades to provide space for wound repair, avoiding damage to the new tissue caused by secondary removal.

[0084] 1.2.8 Calculation of Encapsulation Efficiency and Drug Loading

[0085] The amount of unencapsulated BAI1 in the supernatant during the preparation process in Example 1 was determined by HPLC. Encapsulation efficiency = (total drug dosage - drug dosage in supernatant) / total drug dosage × 100%; Drug loading = (encapsulated drug dosage / total weight of nanoparticles) × 100%. Calculations showed that...

[0086] Encapsulation efficiency ≈ 45.1%;

[0087] Drug loading content ≈ 8.15%;

[0088] The encapsulation efficiency calculations demonstrate that the loading method of this invention effectively overcomes the loading barrier caused by the hydrophobicity of BAI1, allowing drug molecules to successfully enter the ordered mesoporous channels of the MSN through hydrophobic interactions and capillary effects. The drug loading calculations show that the MSN carrier has sufficient pore volume and specific surface area, providing ample loading space for BAI1 and avoiding the problem of requiring large amounts of dressing to achieve an effective therapeutic dose due to insufficient drug loading. This demonstrates good practical application feasibility.

[0089] 2. Application of the composite delivery system BAI1-PSTB in skin wounds of diabetic mice

[0090] Eight-week-old male db / db mice and wild-type C57BL / 6 mice (approximately 40-50 g in weight) were anesthetized via intraperitoneal injection of 1% sodium pentobarbital (50 mg / kg). After hair removal and disinfection with povidone-iodine on the back, a full-thickness skin defect (reaching the fascia) was created in the center of the back using an 8 mm diameter skin biopsy punch. The db / db mice were then randomly divided into three groups (n=5): a diabetic control group (db / db), a blank hydrogel group (db / db+PSTB-Hydrogel), and a BAI1-PSTB hydrogel group (db / db+BAI1-PSTB-Hydrogel). Wild-type C57BL / 6 mice were used as the wild-type C57BL / 6 control group (WT). The wound edges of each group were fixed with silicone rings to reduce interference from skin contraction.

[0091] Then, the wounds of the WT and db / db groups were not covered with any hydrogel material, but only covered with sterile gauze moistened with sterile saline. A Tegaderm transparent film dressing was then applied over the gauze to maintain a moist environment and prevent external contamination. For the db / db+PSTB-Hydrogel group, approximately 0.1 g of blank PSTB hydrogel without any active ingredients was evenly applied to the wound. The gel was gently smoothed using a sterile spatula, ensuring that it completely filled the depressions in the wound and protruded slightly above the surrounding skin surface by about 1 mm. The db / db+BAI1-PSTB-Hydrogel group was given approximately 0.1 g of the BAI1-PSTB composite delivery system prepared in Example 1 of this invention, applied using the same method as described above. All wounds covered with hydrogel were then covered with a layer of sterile petrolatum gauze to prevent excessive evaporation of moisture. The outermost layer was secured in a ring with sterile gauze and medical breathable tape, with the tightness adjusted to not affect the mice's breathing and activity. Dressings were changed every two days for each group. Wound area was photographed and recorded on days 0, 3, 7, 10, and 14, and the percentage of remaining area was calculated using ImageJ software; results are as follows. Figure 10 As shown.

[0092] pass Figure 10Figure A shows that the wound area was consistent across groups on day 0, indicating good uniformity in the modeling process. From day 3 onwards, the wound in the WT group shrank significantly; the wound shrinkage in the db / db group and the db / db+PSTB-Hydrogel group was extremely limited and there was no significant difference between the two; the wound shrinkage in the db / db+BAI1-PSTB-Hydrogel group was better than that in the db / db group. On days 7 and 10, the wound healing in the db / db+BAI1-PSTB-Hydrogel group was significantly accelerated, with the wound color changing from bright red to pink and the epithelial coverage significantly increasing. By day 14, the wounds in the WT group and the db / db+BAI1-PSTB-Hydrogel group were almost completely closed, while the db / db group and the db / db+PSTB-Hydrogel group still had a relatively large area of ​​residual wound.

[0093] pass Figure 10 Figures B and C show that the WT group exhibited a sustained and stable healing trend, with the wound almost completely closed by day 14. There was no statistically significant difference in the percentage of remaining wound area between the db / db group and the db / db+PSTB-Hydrogel group at any time point (P>0.05), indicating that the blank hydrogel did not have healing-promoting activity. From day 7 onwards, the remaining wound area in the db / db+BAI1-PSTB-Hydrogel group was significantly smaller than that in the db / db group (*P<0.05), with a highly statistically significant difference between days 10 and 14 (**P<0.01). The healing rate reached 98.6% by day 14, quantitatively confirming the significant healing-promoting effect of the BAI1-PSTB composite delivery system. Figure 10 The D-values ​​in the data showed that the epidermis in the WT group was intact and continuous, with sparse inflammatory cell infiltration in the dermis; the db / db group and the db / db+PSTB-Hydrogel group still showed obvious epithelial defects, diffuse infiltration of a large number of inflammatory cells in the dermis, and disordered arrangement of fibroblasts; the db / db+BAI1-PSTB-Hydrogel group showed that re-epithelialization was basically completed, the epidermis was continuous, inflammatory cell infiltration was significantly reduced, and the arrangement of fibroblasts tended to be orderly. The results indicate that the BAI1-PSTB composite delivery system can effectively promote re-epithelialization of diabetic wounds and inhibit local inflammatory responses.

[0094] pass Figure 10The E-mode showed that collagen fibers in the dermis of the WT group were tightly packed and regularly oriented, exhibiting a homogeneous, deep blue deposition. In the db / db and db / db+PSTB-Hydrogel groups, collagen fibers were sparse, broken, and disorganized, with a significant reduction in the blue area. The db / db+BAI1-PSTB-Hydrogel group showed significantly increased collagen fiber deposition, with a more regular arrangement, and both the area and staining intensity of the blue area were significantly better than the two diabetic control groups. These results indicate that the BAI1-PSTB composite delivery system promotes mature and orderly collagen deposition in diabetic wounds, which is beneficial in reducing scar formation. Figure 10 The F-values ​​in the data show that CD31-positive cells were scarce and microvessel density was extremely low in the wound tissue of the db / db group and the db / db+PSTB-Hydrogel group. The area of ​​CD31-positive stained regions and microvessel density in the wound tissue of the db / db+BAI1-PSTB-Hydrogel group were significantly higher than those in the db / db group and the db / db+PSTB-Hydrogel group, and erythrocytes were visible within some of the neovascularization lumens. These results indicate that the BAI1-PSTB composite delivery system can significantly promote angiogenesis in diabetic wounds and improve blood perfusion and nutrient supply to the wound tissue.

[0095] pass Figure 10 The GI analysis showed that the db / db+BAI1-PSTB-Hydrogel group had a significantly lower inflammatory cell infiltration score, a significantly higher percentage of collagen deposition area and microvessel density, and significantly lower percentages of BAX, STING, and p16 positive areas compared to the diabetic control group (P<0.01 or **P<0.001). These results collectively indicate that the BAI1-PSTB composite hydrogel, by targeting and inhibiting the BAX / mtDNA / cGAS-STING aging-related inflammatory pathway, comprehensively reverses the pathological microenvironment of diabetic wounds, significantly promoting wound healing and improving healing quality.

[0096] 3. Application of the composite delivery system BAI1-PSTB in infected wound models

[0097] Eight-week-old male C57BL / 6 mice were used. An 8 mm diameter dorsal wound was prepared using the same method described in Part 2 above. The perforated C57BL / 6 mice were then randomly divided into four groups (n=6): normal control (NC), untreated infection group (InfectedWound), growth factor gel group, and BAI1-PSTB hydrogel group (BAI1-PSTB-Hydrogel). The InfectedWound, Growth Factor, and BAI1-PSTB-Hydrogel groups were all inoculated with 10 μL of Staphylococcus aureus suspension (1×10⁻⁶) at the wound site. 7(CFU / mL), a biofilm infection model was formed 2 days after infection.

[0098] For the NC group, the wound was gently rinsed with sterile gauze soaked in sterile saline to remove surface exudate, then the surrounding moisture was absorbed with sterile cotton swabs. The wound was then covered with Vaseline gauze, and secured with sterile gauze and breathable tape. For the Infected Wound group, the wound was similarly rinsed with sterile saline to remove free bacteria and necrotic exudate, while preserving the existing biofilm structure. It was then directly covered with sterile Vaseline gauze and an outer gauze dressing. For the Growth Factor group, after rinsing the wound with saline, approximately 0.1 g of recombinant human epidermal growth factor gel (E-F, Guilin Huanowei Gene Pharmaceutical Co., Ltd.) was evenly applied to the wound using a sterile spatula, ensuring the gel completely filled the wound depressions, before covering with Vaseline gauze and an outer fixation dressing. For the BAI1-PSTB-Hydrogel group, after rinsing with saline, approximately 0.1 g of recombinant human epidermal growth factor gel was evenly applied. The BAI1-PSTB composite delivery system prepared in Example 1 of this invention was applied using the same method as the previous group, ensuring close adhesion between the gel and the wound. It was also covered with Vaseline gauze and an outer sterile dressing. Dressings were changed every two days for each group. Wound area was photographed and recorded on days 0, 2, 5, 8, 10, and 13. Results are as follows... Figure 11 As shown.

[0099] pass Figure 11 The AC study showed that the BAI1-PSTB hydrogel group healed significantly faster than the growth factor gel group: on day 13, the wound area in the BAI1-PSTB hydrogel group decreased by approximately 90%, while that in the growth factor gel group was only reduced by approximately 70%. Figure 11 The DF (Digital Functional Analysis) results showed that the BAI1-PSTB hydrogel group exhibited reduced inflammatory infiltration, richer collagen deposition, and higher angiogenesis density. These results indicate that the composite delivery system BAI1-PSTB prepared in this invention is superior to existing clinical products in the treatment of infected wounds.

[0100] Although embodiments of the invention have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the claims and their equivalents.

Claims

1. A polyvinyl alcohol-sodium alginate-tannic acid-borax hydrogel composite delivery system for BAI1-loaded mesoporous silica, characterized in that, The composite delivery system includes a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel and BAI1-mesoporous silica lyophilized powder encapsulated within it. The polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel is formed by cross-linking polyvinyl alcohol, sodium alginate, tannic acid and borax; The BAI1-mesoporous silica freeze-dried powder includes mesoporous silica nanoparticles and BAI1 loaded in its mesopores.

2. The composite delivery system according to claim 1, characterized in that, The mass ratio of polyvinyl alcohol, sodium alginate, tannic acid and borax is 5-15 : 1-5 : 0.5-3 : 0.5-2.

3. The composite delivery system according to claim 1, characterized in that, The mass ratio of BAI1 to mesoporous silica nanoparticles is 0.5-2:

1.

4. A method for preparing a composite delivery system according to any one of claims 1-3, characterized in that, include: Weigh BAI1 and mesoporous silica nanoparticles according to the mass ratio, and prepare BAI1 solution and mesoporous silica dispersion respectively; BAI1 solution was added to mesoporous silica dispersion and stirred at room temperature for 24 hours. After centrifugation and washing multiple times, cryoprotectant and deionized water were added to the precipitate, mixed well, and pre-frozen at -80℃ for 4 hours. Then, it was freeze-dried to obtain BAI1-mesoporous silica freeze-dried powder. Weigh out polyvinyl alcohol, sodium alginate, tannic acid and borax according to the mass ratio. Prepare polyvinyl alcohol solution and borax solution respectively. Add sodium alginate to polyvinyl alcohol solution and stir for 1 hour. Then add tannic acid and continue stirring for 30 minutes. Adjust the pH to 8.0 to obtain a mixed solution. BAI1-mesoporous silica lyophilized powder was added to the mixed solution and stirred for 30 minutes. Then, borax solution was added while stirring. After the addition was completed, stirring was continued for 1 minute and the mixture was allowed to stand for 30 seconds to obtain a polyvinyl alcohol-sodium alginate-tannic acid-borax composite hydrogel with BAI1-mesoporous silica lyophilized powder inside, which is the composite delivery system.

5. The method according to claim 4, characterized in that, The mass ratio of the cryoprotectant to the mesoporous silica nanoparticles is 0.2:

1.

6. The method according to claim 4, characterized in that, The freeze-drying pressure is <10 Pa, and the freeze-drying temperature and time are -50℃ and 48 hours, respectively.

7. The method according to claim 4, characterized in that, The mass ratio of the BAI1-mesoporous silica freeze-dried powder to polyvinyl alcohol is 1-6 : 5-15.

8. The use of a composite delivery system according to any one of claims 1-3 in the preparation of a dressing for the repair of diabetic wounds.

9. A dressing for the repair of diabetic wounds, characterized in that, Includes the composite delivery system as described in any one of claims 1-3.